Influencia de las dosis de ceniza de madera, en las características agronómicas y rendimiento de Capsicum annuum L. "pimiento", Zungarococha - Loreto. 2019 - Davila Rengifo, Darletty Jaclyn Jeanette (2022)
The study on the "Influence of wood ash doses, on the agronomic characteristics and yield of Capsicum annuum L. "pepper", Zungarococha-Loreto. 2019", was carried out in the experimental field of the vegetable area of the Faculty of Agronomy-UNAP, in order to determine the influence of wood ash doses on the agronomic characteristics and yield of Capsicum annuum L. "pepper".The experimental design handled was that of Completely Random Blocks and the Tukey Comparison Test. Each experimental plot of the 16, was constituted by 10 plants. With the results obtained, the following conclusions were reached: Fertilization with wood ash in Capsicum annuum L. "pepper", statistically influenced the agronomic components and yield of the crop; treatment T4 (3 t of wood ash/ha, presented the highest average value of weight of fruits/ha, with 36.88 t and also presented the best utility with S/.209,356.00